Snobbery : - Epstein, Joseph (Houghton Mifflin, 2002)
Joseph Epstein's witty new book surveys American snobbery after the fall of the old Wasp culture of prep schools, Ivy League colleges, cotillions, debutante balls, the Social Register, and the rest of it. With ample humor and insight, Epstein uncovers the new outlets upon which the old snobbery has fastened: food and wine, fashion, high-achieving children, schools, politics, health, being with-it, name-dropping, and much else, including the roles of Jews and homosexuals in the development of snobbery. Playing throughout Snobbery: The American Version is the question of whether snobbery is part of human nature.